Atezolizumab in Patients with Pretreated Urothelial Cancer: a Korean Single-Center, Retrospective Study - Hur, Joon Young; Kim, Youjin; Kwon, Ghee-Young; Kang, Minyong; Sung, Hyun Hwan; Jeon, Hwang Gyun; Jeong, Byong Chang; Seo, Seong Il; Jeon, Seong Soo; Lee, Hyun Moo; Lee, Su Jin; Park, Se Hoon (Cancer research and treatment, 2019)
Treatment targeting immune checkpoint with programmed death-1 (PD-1)/programmed death-ligand 1 (PD-L1) inhibitors has demonstrated efficacy and tolerability in the treatment of metastatic urothelial carcinoma (mUC). We investigated the efficacy and safety of atezolizumab in mUC patients who failed platinum-based chemotherapy. A retrospective study using the Samsung Medical Center cancer chemotherapy registry was performed on 50 consecutive patients with mUC treated with atezolizumab, regardless of their PD-L1(SP142) status, as salvage therapy after chemotherapy failure between May 2017 and June 2018. Endpoints included overall response rate (RR), progression-free survival (PFS), and safety. Among 50 patients, men constituted 76% and the median age was 68 years (range, 46 to 82 years). Twenty-three patients (46%) received atezolizumab as second-line therapy. PD-L1 (SP142) status IC0/1 and IC2/3 were found in 21 (42%) and 21 (42%) of patients, respectively; in eight patients (16%), PD-L1 (SP142) expression was not available. Atezolizumab was generally well tolerated, with pruritus and fatigue being the most commonly observed toxicities. As a result, partial response was noted in 20 patients (40%), with 12 (24%) stable diseases. RRwas higherin IC2/3 (62%) than in IC0/1 patients (24%, p=0.013). The median PFS was 7.4 months (95% confidence interval, 3.4 to 11.4 months). As expected, PFS also was significantly longer in IC2/3 patients than in IC0/1 (median, 12.7 vs. 2.1 months; p=0.005). PFS was not significantly influenced by age, sex, performance status, number of previous chemotherapy, site of metastases, or any of the baseline laboratory parameters. In this retrospective study, atezolizumab demonstrated clinically efficacy and tolerability in unselected mUC patients who failed platinum-based chemotherapy.